Isfahan and Its Palaces : statecraft, Shi'ism and the architecture of conviviality in early modern Iran - Babaie, Sussan (Edinburgh studies in Islamic art., 2018)
This beautifully illustrated history of Safavid Isfahan (1501-1722) explores the architectural and urban forms and networks of socio-cultural action that reflected a distinctly early-modern and Perso-Shi'i practice of kingship.